Friction nano-generator connected with electron cloud potential well to improve output current and preparation method and application of friction nano-generator

By embedding an rGO conductive network in the triboelectric layer and connecting the electronic cloud potential well, the problem of TENG's performance degradation in high humidity and rainy environments is solved, and EL-TENG with high output current and moisture resistance is achieved.

CN119561413AActive Publication Date: 2025-03-04NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411780002.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-04
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

Existing triboelectric nanogenerators (TENGs) have challenges in improving output current and moisture resistance, especially in high humidity and rainy environments.

Method used

By embedding a conductive network of reduced graphene oxide (rGO) into the triboelectric layer of ethyl cellulose (EC) and polydimethylsiloxane (PDMS), the electron cloud potential well is connected to form a high-performance friction nanogenerator EL-TENG.

Benefits of technology

It achieves an open circuit voltage of up to 2500 V and a short circuit current of 3000 μA, and can operate stably in high humidity and rainy environments, significantly improving the output current and moisture resistance of TENG.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119561413A_ABST
    Figure CN119561413A_ABST
Patent Text Reader

Abstract

The invention relates to a friction nano-generator connected with an electron cloud potential well to realize high output current. A conductive network-reduced graphene oxide (rGO) capable of being connected with various dielectric polymer segment electron cloud potential wells is embedded into two dielectric layers of ethyl cellulose (EC) and polydimethylsiloxane (PDMS), wherein the electronegativity difference of the two dielectric layers is large. Results show that in the operation process of TENG, more charges can be transferred from one triboelectric material to another material. The TENG based on the model shows a recorded 3000 [mu] A high output current in a contact separation mode. In addition, the TENG shows excellent durability in a high-humidity environment, which is a huge challenge for the traditional TENG. The invention provides a novel and promising strategy for manufacturing the TENG with ultrahigh output current and water resistance, which is crucial for further development and practical application of the TENG.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a friction nanogenerator connected to an electron cloud potential well to increase output current, and belongs to the field of energy collection. Background Art

[0002] Triboelectric nanogenerators (TENGs) are based on the combination of friction electrification and electrostatic induction, which can convert irregular, low-frequency, and ubiquitous mechanical energy into electrical energy. So far, TENGs have shown great application prospects in micro-nano power supply, self-powered sensing, and blue energy harvesting. Improving output performance and operating stability are the core of TENG development. In order to improve the triboelectric performance of TENGs, many strategies have been developed, including surface microstructure, molecular design, filling of high dielectric or high electric negative / positive materials, etc. With these strategies, the output voltage has been improved by several orders of magnitude to the kV level. However, due to the limited charge transfer between the friction layers, the improvement of TENGs output current is still not large enough. Several attempts have been made to improve the charge transfer efficiency to improve the output current. Avoiding vacuum breakdown and reducing the impedance of the friction circuit are two typical methods. But the application conditions are harsh and the device structure is complex.

[0003] In the past year, we developed a new strategy to improve the charge transfer efficiency of TENG by matching the density of states between friction layers. As a result, 1333 mA m -2 However, it is challenging to further increase the output using this strategy due to the small electronegativity difference of the friction layer. Therefore, it is still crucial to develop new strategies to obtain higher output current.

[0004] On the other hand, moisture resistance or waterproofing is another requirement for the practical application of TENGs in complex environments. In high humidity or rainy environments, the performance of conventional TENGs usually drops significantly due to the leakage of charges from the friction layer into the air. Efforts have been made to improve the moisture resistance and waterproofing of materials. For example, the surface of the friction layer can be made hydrophobic through material selection or surface engineering to improve the stability of TENGs when the humidity is below 80-85%. However, the performance of TENGs usually still drops significantly in ultra-high humidity environments. Therefore, it is still a huge challenge to design and manufacture high-performance TENGs that can work stably in ultra-high humidity and rainy environments. Summary of the invention

[0005] The technical problem solved by the present invention is: a new strategy is proposed to improve the output current and moisture resistance of TENGs by connecting the electron cloud potential wells of the polymer segment in the triboelectric layer. The conductive network of reduced graphene oxide (rGO) is embedded in the triboelectric layer of ethyl cellulose (EC) and polydimethylsiloxane (PDMS), two materials with a large difference in electronegativity. The TENG obtained by connecting the electron clouds, called EL-TENG, shows a high output current due to the involvement of more electron cloud wells in the contact electrification process. The prepared EL-TENG has a high open circuit voltage (V OC ) and 3000 μA high short-circuit current (I SC ). Due to the new working mechanism, our EL-TENG can work stably in high humidity and rainy environments, which is a big challenge for conventional EL-TENG. The advantages of EL-TENG will greatly promote its practical applications in energy harvesting and self-powered sensing.

[0006] In order to solve the above technical problems, the technical solution proposed in the present invention is: a method for preparing a friction nanogenerator that connects an electron cloud potential well to achieve high output current, comprising the following steps:

[0007] (1) Reduced graphene oxide (rGO) was uniformly dispersed in ethyl cellulose (EC) solution to prepare an EC / rGEC / rGO suspension with a mass fraction of 0.5-0.9 wt%. The prepared suspension was poured into a polytetrafluoroethylene (PTFE) mold and then annealed in a vacuum oven. The obtained EC / rGO composite film was peeled off to serve as the positive triboelectric material of TENG.

[0008] (2) Dispersing rGO uniformly in a polydimethylsiloxane (PDMS) precursor to prepare a PDMS / rGO suspension with a mass fraction of 0.4-1 wt %; pouring the prepared suspension into a culture dish and drying it to obtain a PDMS / rGO composite film as the triboelectric material of TENG;

[0009] (3) Cutting the obtained EC / rGO and PDMS / rGO membranes into appropriate sizes;

[0010] (4) PDMS / rGO and EC / rGO films cut into appropriate sizes were used as the triboelectric layers in EL-TENG. The two triboelectric layers were glued onto two copper foils to assemble a triboelectric nanogenerator EL-TENG that works in the contact-separation mode and connects the electron cloud potential well to achieve high output current.

[0011] Preferably, the method comprises the following steps: dissolving EC in ethanol at 60°C to obtain a 10 wt% solution, mixing 5 mL of a 10 wt% 3-glycidyloxypropyltrimethoxysilane solution with 50 mL of an EC solution; uniformly dispersing reduced graphene oxide in the EC solution to prepare EC / rGO suspensions with mass fractions of 0.5, 0.7 and 0.9 wt%, respectively, pouring the prepared suspensions into a polytetrafluoroethylene mold, and then annealing at 60°C in a vacuum oven for 12 h; peeling off the obtained EC / rGO composite film as a positive triboelectric material of TENG; adjusting the thickness of different EC / rGO films by adjusting the depth of the groove inside the mold to 0.1 mm-1 mm;

[0012] The polydimethylsiloxane (PDMS) precursor and the curing agent were mixed in a mass ratio of 10:1; rGO was uniformly dispersed in the PDMS precursor to prepare PDMS / rGO suspensions with mass fractions of 0.4, 0.6, 0.8 and 1 wt %, respectively; the prepared suspension was poured into a culture dish and dried at 60 °C for 12 h to obtain a PDMS / rGO composite membrane; the thickness of different PDMS / rGO membranes was adjusted by adjusting the depth of the internal groove of the mold to 0.1 mm-1 mm; the obtained EC / rGO and PDMS / rGO membranes were cut into appropriate sizes of 3 × 3 cm 2 ;

[0013] 3 × 3 cm 2 The PDMS / rGO and EC / rGO films of different sizes were then used as the triboelectric layers in the EL-TENG, and the two triboelectric layers were glued onto two pieces of copper foil to assemble the EL-TENG working in the contact-separation mode.

[0014] Preferably, ethyl cellulose EC, viscosity μ = 3-7 mPa·s. Polydimethylsiloxane PDMS, Sylgard184.

[0015] Preferably, reduced graphene oxide rGO, specific surface area = 66 m 2 , conductivity = 19 S cm -1 .

[0016] Preferably, when the ratio of rGO doped in PDMS solution is 1 wt %, the thickness of EC / rGO membrane is 0.6 mm, the thickness of PDMS / rGO membrane is 0.6 mm, and the ratio of rGO doped in EC is 0.9 wt %, the initial distance between the friction layers is 6 mm, the operating frequency is 5 Hz, and the output voltage of the prepared friction nanogenerator is 2500 V, and the output current is 3000 μA.

[0017] In order to solve the above technical problems, another technical solution proposed by the present invention is: a high-performance rainproof friction nanogenerator prepared by any method.

[0018] In order to solve the above technical problems, another technical solution proposed by the present invention is: the application of the high-performance rainproof friction nanogenerator can also perform well in a high humidity environment and in the rain.

[0019] Preferably, it is applied to efficient energy harvesting and self-powered motion sensing in rain.

[0020] Preferably, it is applied in the fields of personal health monitoring, patient rehabilitation, exercise monitoring and human motion tracking.

[0021] Beneficial effects of the present invention:

[0022] The present invention proposes a new method to improve the output current and moisture resistance of TENGs by connecting the electron cloud potential wells of the polymer segment in the triboelectric layer.

[0023] Herein, we fabricated a triboelectric TENG by embedding a conductive network of reduced graphene oxide (rGO) into triboelectric layers of ethyl cellulose (EC) and polydimethylsiloxane (PDMS), two materials with large electronegativity differences. The TENG obtained by connecting the electron clouds, called EL-TENG, showed high output current due to the involvement of more electron cloud traps during contact electrification. The prepared EL-TENG has a high open circuit voltage (V OC ) and 3000 μA high short-circuit current (I SC ).

[0024] When the ratio of rGO doped in PDMS solution was 1 wt % and the ratio of rGO doped in EC was 0.9 wt %, the initial distance between the friction layers was 6 mm, the operating frequency was 5 Hz, the thickness of EC / rGO membrane was 0.6 mm, and the thickness of PDMS / rGO membrane was 0.6 mm, the best electrical performance (output voltage of 2500 V, output current of 3000 μA) was obtained.

[0025] Due to the new working mechanism, our EL-TENG can work stably in high humidity and rainy environments, which is a big challenge for conventional EL-TENG. The advantages of EL-TENG will greatly promote its practical applications in energy harvesting and self-powered sensing. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1Design and output performance of EL-TENG. (a) Schematic diagram of the device structure of conventional dielectric TENG. (b) ECPW model of conventional dielectric TENG based on EC and PDMS, (c) Schematic diagram of the device structure of the EL-TENG of the present invention. (d) Schematic diagram of the connection of the electron cloud potential wells of the EC layer and the PDMS layer in the EL-TENG through the conductive network of reduced graphene oxide (rGO) sheets. (e) Simulation of the electron density at the interface of PDMS / rGO and EC / rGO. (fh) Output (f) voltage, (g) current, (h) charge of TENGs (size = 3 × 3 cm2) based on EC-PDMS and EC / rGO-PDMS / rGO. (i) Output voltage and current of EL-TENG based on EC / rGO-PDMS / rGO with different thicknesses. (j) Comparison of the current density of the EL-TENG of the present invention with the reported current density of TENGs working in contact-separation mode.

[0027] Figure 2 Performance optimization of EL-TENG. (a) Resistance of EC / rGO and PDMS / rGO films with different rGO contents. (bc) Output (b) voltage and (c) current of EL-TENG based on EC / rGO and PDMS / rGO with different rGO loadings. (df) Performance of EL-TENG at different (d) initial separation distances and (e, f) operating frequencies. (g) Output voltage stability of EL-TENG over 5000 cycles.

[0028] Figure 3 Performance of EL-TENG in high humidity and rainy environment. (ab) Peak voltage and current of (a) TENG based on dielectric material (PDMS-EC) and (b) EL-TENG when relative humidity changes from 20% to 100%. (c) Water contact angle of EC, EC / rGO, PDMS, and PDMS / rGO films. (d) Schematic diagram of charge leakage in dielectric TENG and (e) Schematic diagram of charge leakage suppression in EL-TENG. (fg) Output (f) voltage and (g) current of EL-TENG in rainy environment.

[0029] Figure 4Application demonstration of EL-TENG as an energy supplier. (ab) Output voltage and current of (a) EL-TENG and (b) dielectric TENG (PDMS-EC) under different external loads. (c) Power of EL-TENG and dielectric TENG under different external loads. (d) Circuit diagram of EL-TENG equipped with energy storage unit for powering thermohygrometer. (e) Voltage curves of 100, 220, 470 μF and 1 mF capacitors charged by EL-TENG. (f) Voltage-time curve of thermohygrometer powered by EL-TENG. Inset: Photo of power management system. (g) Circuit diagram and (h) photo (inset) of 2688 LEDs connected in series powered by EL-TENG. (i) Comparison with the number of LEDs lit by TENGs in contact-separation mode (normalized to the surface area of ​​TENGs) reported.

[0030] Figure 5 Demonstration of the application of EL-TENG as a self-powered wearable sensor. (a) Schematic diagram of the self-powered sensor installed on the human body. (b) Monitoring the motion state of EL-TENG by detecting the bending of sweaty hands. (c) Monitoring the motion state of EL-TENG by detecting the bending of sweaty elbows. (d) Monitoring the motion state of EL-TENG by detecting the bending of sweaty knees. Output current signals of EL-TENG monitoring different human motion states, including (e) walking, (f) running, and (g) jumping. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with the accompanying drawings.

[0032] Example 1

[0033] Preparation of EL-TENG:

[0034] Ethyl cellulose (EC) with a viscosity of μ = 3-7 mPa·s (Aladdin) was prepared by dissolving EC powder in ethanol at 60 °C to obtain a 10 wt% solution. Then, 5 mL of a 10 wt% solution of 3-glycidyloxypropyltrimethoxysilane was mixed with 50 mL of the EC solution. Finally, reduced graphene oxide (rGO, surface area = 66 m 2 , conductivity = 19 S cm -1 ) were uniformly dispersed in the EC solution to prepare EC / rGO suspensions with mass fractions of 0, 0.1, 0.3, 0.5, 0.7 and 0.9 wt%, respectively.

[0035] The prepared suspension was poured into a polytetrafluoroethylene (PTFE) mold and then annealed in a vacuum oven at 60 °C for 12 h. The obtained EC / rGO composite film was peeled off and used as the positive triboelectric material of TENG. The different thicknesses were adjusted by adjusting the depth of the internal groove of the mold to adjust the thickness of the EC / rGO film to 0.1 mm-1 mm.

[0036] The polydimethylsiloxane (PDMS, Sylgard 184) precursor and curing agent were mixed in a mass ratio of 10:1. Then, rGO was uniformly dispersed in the PDMS precursor to prepare PDMS / rGO suspensions with mass fractions of 0, 0.1, 0.2, 0.4, 0.6, 0.8 and 1wt%, respectively. The prepared suspension was poured into a culture dish and dried at 60°C for 12 h to obtain a PDMS / rGO composite membrane. Different thicknesses were adjusted by adjusting the depth of the internal groove of the mold to adjust the thickness of different PDMS / rGO membranes by 0.1mm-1mm. The obtained EC / rGO and PDMS / rGO membranes were cut into suitable sizes (usually 3 × 3 cm 2 ), used to assemble EL-TENG. The process is as follows:

[0037] EL-TENG is manufactured using a simple assembly process. Typically, a 3 × 3 cm 2 The PDMS / rGO and EC / rGO films were then used as the triboelectric layers in the EL-TENG. The two triboelectric layers were glued onto two pieces of copper foil. Finally, the EL-TENG operating in the contact-separation mode was assembled.

[0038] Preparation of TENG:

[0039] EC was dissolved in ethanol at 60 °C to obtain a 10 wt% solution. Then, 5 mL of 10 wt% 3-glycidyloxypropyltrimethoxysilane solution was mixed with 50 mL of EC solution. The prepared EC suspension was poured into a PTFE mold and then annealed at 60 °C in a vacuum oven for 12 h. The obtained EC film was peeled off and used as the positive triboelectric material of TENG. Different thicknesses were adjusted by adjusting the depth of the groove inside the mold to adjust the thickness of different EC films.

[0040] The polydimethylsiloxane precursor and curing agent were mixed in a mass ratio of 10:1. The prepared suspension was poured into a petri dish and dried at 60 °C for 12 h to obtain a PDMS membrane. The different thicknesses were adjusted by adjusting the depth of the groove inside the mold to adjust the thickness of the different PDMS membranes.

[0041] The obtained EC / PDMS membranes were cut into appropriate sizes (usually 3 × 3 cm 2 ).

[0042] 3 × 3 cm 2 The two friction layers of PDMS and EC were glued to two copper foils. Finally, the TENG working in the contact-separation mode was assembled.

[0043] In TENG, when two friction layers come into contact with each other, contact electrification occurs at the interface, and the generated charges can be collected by an external circuit. Typically, the friction layer in TENG is usually composed of dielectric polymers, which are usually composed of polymer chains ( Figure 1 a).

[0044] Figure 1 As shown. Design and output performance of EL-TENG. (a) Schematic diagram of the device structure of conventional dielectric TENG. The inset shows the polymer chains within the friction layer. (b) ECPW model of conventional dielectric TENG based on EC and PDMS, with limited electron transfer at the interface. (c) Schematic diagram of the device structure of our EL-TENG. The inset shows the polymer chains within the friction layer embedded in graphene oxide. (d) Schematic diagram of the connection of the electron cloud potential wells of the EC layer and the PDMS layer in the EL-TENG through the conductive network of reduced graphene oxide (rGO) sheets, and the electron transfer at the interface is greatly enhanced. (e) Simulation of the electron density of the PDMS / rGO and EC / rGO interfaces, showing the electron transfer at these interfaces. Yellow and cyan represent the positive and negative electron density differences, respectively. (fh) TENG based on EC-PPDMS and EC / rGO-PDMS / rGO (size = 3 × 3 cm 2 )’s output (f) voltage, (g) current, and (h) charge. (i) Output voltage and current of EL-TENG based on EC / rGO-PDMS / rGO with different thicknesses. (j) Comparison of the current density of our EL-TENG with that of the reported TENG working in contact-separation mode.

[0045] In TENG, when two friction layers come into contact with each other, contact electrification occurs at the interface, and the generated charges can be collected by an external circuit. Typically, the friction layer in TTENG is usually composed of dielectric polymers, which are usually composed of polymer chains ( Figure 1 a). Based on the ECPW model, a dielectric polymer can be regarded as multiple ECPWs, and the filling energy level of this hole (also called Fermi level) is related to the electron affinity of the material. Contact electrification can be explained as the transfer of electrons from the ECPW on the surface of one friction layer to the surface of another friction layer, and the partial overlap of the ECPWs of the two opposing friction layers is a prerequisite for electron transfer ( Figure 1b). On the contrary, a larger difference in the Fermi levels of the triboelectric layers will result in more charge transfer during contact electrification. However, the number of electrons in the ECPW is limited, and only the electrons on the surface of the triboelectric layer can promote contact electrification ( Figure 1 b).

[0046] If we can connect many ECPWs in the triboelectric layer together (especially the ECPWs inside the triboelectric layer), the generated charges and the output current of the TENG will be significantly enhanced ( Figure 1 d).

[0047] To verify our proposal, density functional theory (DFT) simulations were performed using CP2K. To reduce the required computational resources, we used rGO to represent rGO flakes and short PDMS and EC chains to represent long polymer chains in our calculations. Electron density difference (EDD) images showed that electrons in EC can be transferred to rGO at the EC / rGO interface ( Figure 1 e), indicating that electrons in many EC chains inside the EC / rGO layer can accumulate and then be directed to the EC film surface through the rGO sheets. Therefore, during the contact electrification process with more electrons on the surface, improved charge transfer between the tribolayers can be achieved. Similar results were obtained in the EDD image of the PDMS / rGO interface, where electrons in the PDMS can accumulate on the rGO sheets. These results validate our hypothesis that doped graphene oxide sheets can greatly improve the charge transfer from EC to PDMS during contact electrification.

[0048] We compared the output performance of rGO-embedded EL-TENG with that of TENG without rGO embedding ( Figure 1 f-1h). Compared with the TENG based on EC and PDMS friction pair, the V OC Increase from 300 V to 2500 V ( Figure 1 f). In contrast, the I SC Significant increase from 60 μA to 3000 μA ( Figure 1 g), which is 50 times that of the dielectric TENG based on the EC-PDMS tribocouple. On the other hand, the output charge increases from 30 nC to 800 nC ( Figure 1 h), This 26.7-fold increase highlights the significant contribution of the rGO conductive network to the output charge of the EL-TENG, confirming the validity of our hypothesis.

[0049] To further confirm our hypothesis, we investigated the effect of film thickness on output performance in conventional TENG and our EL-TENG. In conventional TENG, output performance generally decreases with increasing friction layer thickness because thinner friction layers can promote electrostatic induction. We verified this phenomenon in a TENG composed of EC and PDMS. As the friction layer thickness increases from 0.1 mm to 1 mm, V OC From 300 V to 60 V, while I SC From 80 μA to 5 μA. This is completely different in our EL-TENG. As the thickness of EC / rGO and PDMS / rGO films increases from 0.1 mm to 1 mm, the V OC It increases linearly from 1200 V to 3300 V, I SC Increases linearly from 600 μA to 4000 μA ( Figure 1 i). The film thickness of 1 mm is difficult to control, so a film thickness of 0.6 mm was used later. The significant difference between the conventional TENG and our EL-TENG suggests that the EL-TENG has a different working mechanism. In the EL-TENG, the thicker film can connect more electron cloud potential wells, so that more charge can be transferred during contact electrification, explaining the increase in output current. The results here double verify our hypothesis that the electron cloud potential wells connecting the polymer segments can significantly increase the output current of the TENG.

[0050] In order to compare the performance of our EL-TENG with that of the reported TENGs, the I SC Normalized to 3533 mAm −2 To the best of our knowledge, this current density is the highest reported for contact-separation mode TENGs ( Figure 1 j). This high current density can be explained by two reasons. First, the electron affinity between EC and PDMS is large. More importantly, the connection of the electron cloud potential wells in the triboelectric layers significantly enhances the amount of charge transferred from one tribolayer to the other.

[0051] Example 2

[0052] Embedding rGO nanosheets into the triboelectric layer can significantly improve the output performance of the corresponding TENG. Obviously, the output performance of the EL-TENG is closely related to the content of rGO nanosheets embedded in the triboelectric layer. We varied the rGO content in the range of 0-1 wt% and studied its effect on the output performance of the corresponding TENG. When the rGO content is higher than 1 wt%, it will agglomerate in EC / PDMS, so we limited the maximum rGO content to 1 wt%. The resistance of EC / rGO and PDMS / rGO changed significantly with the change of rGO content ( Figure 2 a). When the rGO content in the EC film increases from 0 to 0.9 wt%, the resistance of the EC / rGO film decreases significantly to 1 kΩ, which is mainly due to the formation of a conductive network at high rGO content. The conductive rGO nanosheets can connect the electron cloud potential wells of the EC polymer segments. Similarly, when the rGO content increases to 1 wt%, the resistance of the PDMS / rGO film decreases to 1 MΩ.

[0053] Subsequently, EC / rGO and PDMS / rGO films with different rGO contents were used to assemble EL-TENGs operating in contact-separation mode. As the rGO content increased from 0 to 1 wt%, both the output voltage and current increased. The highest V OC (2500 V) and the highest I SC (3000 μA) ( Figure 2 b, 2c). Then, we investigated the factors that affect the output performance of EL-TENG at 1 wt% rGO content. First, the output performance of our EL-TENG depends on the initial distance between the two friction layers. As the initial distance increases from 2 to 6 mm, V OC Increase from 1000 V to 2500 V ( Figure 2 d), I SC Increased from 1200 μA to 3000 μA ( Figure 2 d). These increases are attributed to the faster charge transfer between the friction layers. Further increasing the initial distance weakens the electrostatic induction between the friction layer and the electrode, resulting in a decrease in output performance. Second, we studied the dependence of the EL-TENG output performance on the operating frequency. When the operating frequency increases from 1 Hz to 5 Hz, V OC However, as the operating frequency increases from 1 Hz to 5 Hz, I SC Gradually increase from 700 μA to 3000 μA ( Figure 2e). It is reported that the total charge in the external circuit remains constant at different operating frequencies, thus ensuring a stable output voltage. However, the charge transfer is accelerated at higher frequencies, resulting in an increase in the output current. Our EL-TENG also exhibits excellent stability during operation. After 5000 operating cycles, the output voltage and current are almost unchanged ( Figure 2 f).

[0054] summary:

[0055] When the ratio of rGO doped in PDMS solution was 1wt% and the ratio of rGO doped in EC was 0.9 wt%, the initial distance between the friction layers was 6mm, the thickness of EC / rGO membrane was 0.6mm, the thickness of PDMS / rGO membrane was 0.6mm, and the operating frequency was 5Hz, the best electrical performance (output voltage of 2500V, output current of 3000 μA) was obtained. Subsequent experiments were carried out with this parameter.

[0056] Example 3

[0057] In the following Examples 3 to 5, we selected the EL-TENG prepared with the optimal parameters (when the doping ratio is 1%, the initial distance between the friction layers is 6 mm, and the frequency is 5 Hz).

[0058] In the dielectric TENG, when the relative humidity (RH) increases from 20% to 60%, V OC and I SC It has dropped by about 25% ( Figure 3 a). When RH further increases to 100%, the output performance drops sharply to about 0. In contrast, the output voltage and current of EL-TENG remain stable even when RH increases to 100% ( Figure 3 b) shows excellent moisture resistance.

[0059] Then, we tried to explore the mechanism of the excellent moisture resistance of EL-TENG. In many reports, the moisture resistance of TENGs is improved by making the friction layer surface hydrophobic. In our study, the water contact angle of the EC film embedded with rGO (mass fraction 1%) was reduced from 115° to 109° ( Figure 3 c) Compared with bare PDMS, the water contact angle of the PDMS film embedded with rGO (mass fraction 1%) decreases from 124° to 115°. Therefore, the excellent moisture resistance of our EL-TENG cannot be explained by the hydrophobicity of the friction layer, and there must be a new mechanism to explain the improved performance of our EL-TENG under humidity.

[0060] In conventional dielectric TENGs, the charges generated by contact electrification may leak into the air at high humidity due to the increase in air conductivity ( Figure 3 d). In contrast, due to the embedding of rGO conductive nanosheets ( Figure 3 e) The conductivity of the EC / rGO and PDMS / rGO friction layers in our EL-TENG is greatly increased. Therefore, under high humidity, the conductivity of the friction layer is much greater than that of the air. Therefore, the charge leakage in our EL-TENG to the air will be greatly reduced, explaining its high performance stability under high humidity and rainy environment.

[0061] Due to the new working mechanism, our EL-TENG can even work stably in rainy environments. We used a watering can to simulate light rain, moderate rain, and heavy rain. It was found that the performance of the unencapsulated EL-TENG was almost unchanged in light rain, moderate rain, and heavy rain ( Figure 3 f-3g). In light rain, the EL-TENG shows a V of about 2480 V. OC and about 3000 μA of I SC In the moderate rain, EL-TENG's V OC and I SC They drop slightly to about 2440 V and about 2980 μA respectively. In heavy rain, V OC and I SC It further slightly decreases to about 2320 V and about 2960 μA, which are 93% and 98% of those in the dry environment, respectively. These results indicate that the EL-TENG exhibits high stability in the unencapsulated state in a rainy environment. As far as we know, it is challenging for conventional TENGs to operate stably in a rainy environment. Therefore, this unique feature of our EL-TENGs greatly expands its practical applications.

[0062] Example 4

[0063] Due to the large increase in output current / charge, our EL-TENG shows great advantages in energy harvesting. We first studied the performance of EL-TENG under different external loads. When the resistance of the external load was increased from 10 3 Ω increases to 10 9 Ω, the maximum output voltage of the EL-TENG increases from 1.5 V to 2500 V, while that of the conventional TENG based on bare EC and PDMS pairs increases from 0.1 V to 330 V. 3 Ω increases to 10 9 Ω, the maximum output current of EL-TENG is reduced from 3500 µA to 10 µA, while that of the conventional TENG based on EC and PDMS pair is reduced from 70 µA to 0.6 µA ( Figure 4a, 4b). Under an external load of 500 kΩ, the maximum power is 528 mW, while in the conventional TENG, only 2.83 mW is obtained under an external load of 20 MΩ ( Figure 4 c). These results show that the maximum power obtained by EL-TENG is 186 times that of the traditional dielectric TENG, and the best output is obtained under a smaller electrical load. Therefore, EL-TENG, as an energy harvesting device, can provide higher output power for electrical appliances with small loads.

[0064] Then, we demonstrated the practical applications of EL-TENG in various scenarios. First, EL-TENG charges the capacitor through the rectifier and energy management unit ( Figure 4 d). The 100, 220, 470, and 1000 µF capacitors charge to 1.5V in 1.5, 6, 14, and 27 seconds, respectively ( Figure 4 e). Subsequently, the EL-TENG powered the appliance through a 1000 µF capacitor. The energy generated by the CE-TENG was stored in the capacitor and then used to power the electronic device ( Figure 4 f). During operation, the output voltage exhibits a sawtooth fluctuation centered at 1.5 V. Our EL-TENG also lights up a light-emitting diode (LED) via a circuit diagram with a rectifier ( Figure 4 g). Due to high performance, the size is only 3 × 3 cm 2 The EL-TENG can efficiently light up 2688 LEDs ( Figure 4 h). For comparison, we normalize the number of lit LEDs to about 300 LEDs / cm2, which is much higher than the reported TENGs working in contact-separation mode (which can only light up a few to tens of LEDs / cm2). 2 )( Figure 4 i). More importantly, the above applications can still be performed in high humidity and rainy environments. These applications show that our EL-TENG has great advantages in many applications due to its high output performance and stability.

[0065] Example 5

[0066] Our EL-TENG can also be used as a self-powered wearable sensor. It is well known that the performance of wearable sensors is significantly affected by sweat generated on human skin, especially in motion sensing. This can be very serious in some scenarios, so it is necessary to find self-powered sensors with high waterproofness. Thanks to its excellent waterproof and moisture-proof properties, our EL-TENG can be used as an excellent self-powered sensor in various scenarios. As a demonstration, we fixed the EL-TENG on different parts of the sweating human body to monitor human motion ( Figure 5 a).

[0067] We then fixed the EL-TENG on sweaty human joints to sense joint bending of the hands, elbows, and knees. First, we tested the behavior of the EL-TENG as a self-powered sensor in the absence of sweating on the body surface and found that the frequencies and peaks of the triboelectric signals generated by different joint movements and different motion states of the human body were different, which is also possible in conventional TENG devices. However, since conventional TENGs are not moisture-proof, their performance is usually significantly affected by sweating conditions. In contrast, our EL-TENG is able to stably sense human motion in the presence of sweat. When the human body was sweating, an I of approximately 50 μA was observed during cyclic bending of the hand joints. SC ( Figure 5 b). A higher I of about 110 μA was observed during elbow joint movement. SC ( Figure 5 c). During knee joint motion, an I of approximately 200 μA was observed. SC ( Figure 5 d). In addition, by fixing EL-TENG on the sole, the motion state of the human body can be monitored. EL-TENG successfully monitored various motion states including walking, running and jumping ( Figure 5 e-5g). These results indicate that our EL-TENG is able to convert various physiological characteristics and motion behaviors into readable, quantifiable, and real-time triboelectric signals. Therefore, our EL-TENG can be used to monitor the physiological characteristics and motion behaviors of people who sweat a lot, such as firefighters or astronauts. Our EL-TENG has broad application prospects in the fields of personal health monitoring, patient rehabilitation, sports monitoring, and human motion tracking.

[0068] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.

Claims

1. A method for preparing a triboelectric nanogenerator that connects an electron cloud potential well to achieve high output current, characterized in that : Includes the following steps: (1) Reduced graphene oxide (rGO) was uniformly dispersed in ethyl cellulose (EC) solution to prepare an EC / rGEC / rGO suspension with a mass fraction of 0.5-0.9 wt%. The prepared suspension was poured into a polytetrafluoroethylene (PTFE) mold and then annealed in a vacuum oven. The obtained EC / rGO composite film was peeled off to serve as the positive triboelectric material of TENG. (2) Dispersing rGO uniformly in a polydimethylsiloxane (PDMS) precursor to prepare a PDMS / rGO suspension with a mass fraction of 0.4-1 wt %; pouring the prepared suspension into a culture dish and drying it to obtain a PDMS / rGO composite film as the triboelectric material of TENG; (3) Cutting the obtained EC / rGO and PDMS / rGO membranes into appropriate sizes; (4) The PDMS / rGO and EC / rGO films cut into appropriate sizes are used as the triboelectric layers in the EL-TENG. The two triboelectric layers are glued to two copper foils and assembled into a triboelectric nanogenerator EL-TENG that works in the contact-separation mode and connects the electron cloud potential well to achieve high output current.

2. The method for preparing a triboelectric nanogenerator for connecting an electron cloud potential well to achieve high output current according to claim 1, characterized in that : Includes the following steps: EC was dissolved in ethanol at 60°C to obtain a 10 wt% solution, and 5 mL of 10 wt% 3-glycidyloxypropyltrimethoxysilane solution was mixed with 50 mL of EC solution; reduced graphene oxide was evenly dispersed in the EC solution to prepare EC / rGO suspensions with mass fractions of 0.5, 0.7, and 0.9 wt%, respectively, and the prepared suspensions were poured into a polytetrafluoroethylene mold, and then annealed at 60°C in a vacuum oven for 12 h; the obtained EC / rGO composite film was peeled off and used as the positive triboelectric material of TENG; the thickness of different EC / rGO films was adjusted by adjusting the depth of the internal groove of the mold to 0.1 mm-1 mm; The rGO was uniformly dispersed in the PDMS precursor to prepare PDMS / rGO suspensions with mass fractions of 0.4, 0.6, 0.8 and 1 wt %, respectively. The prepared suspensions were poured into a culture dish and dried at 60 °C for 12 h to obtain a PDMS / rGO composite membrane. The thickness of different PDMS / rGO membranes was adjusted by adjusting the depth of the internal groove of the mold to 0.1 mm-1 mm. The obtained EC / rGO and PDMS / rGO membranes were cut into appropriate sizes of 3 × 3 cm. 2 ; 3 × 3 cm 2 The PDMS / rGO and EC / rGO films of different sizes were then used as the triboelectric layers in the EL-TENG, and the two triboelectric layers were glued onto two pieces of copper foils to assemble into an EL-TENG working in the contact-separation mode.

3. The method for preparing a triboelectric nanogenerator for connecting electron cloud potential wells to achieve high output current according to claim 1, characterized in that: Ethyl cellulose EC, viscosity μ = 3-7 mPa·s, polydimethylsiloxane PDMS, Sylgard184.

4. The method for preparing a high-performance rainproof triboelectric nanogenerator using a charge dispersion strategy according to claim 1, characterized in that: Reduced graphene oxide rGO, surface area = 66 m 2 , conductivity = 19 S cm -1 .

5. The method for preparing a high-performance rainproof triboelectric nanogenerator using a charge dispersion strategy according to claim 1, characterized in that: When the proportion of rGO doped in PDMS solution is 1wt%, the thickness of EC / rGO membrane is 0.6mm, the thickness of PDMS / rGO membrane is 0.6mm, and the proportion of rGO doped in EC is 0.9 wt%, the initial distance between the friction layers is 6mm, the operating frequency is 5Hz, and the output voltage of the prepared friction nanogenerator is 2500V and the output current is 3000 μA.

6. A high-performance rainproof triboelectric nanogenerator prepared according to any one of claims 1-5.

7. The use of the high-performance rainproof tribo-nanogenerator according to claim 6, characterized in that: It also performs well in high humidity environments and in the rain.

8. The use of the high-performance rainproof tribo-nanogenerator according to claim 6, characterized in that: Applications include efficient energy harvesting and self-powered motion sensing in rain.

9. The use of the high-performance rainproof tribo-nanogenerator according to claim 6, characterized in that: It is used in the fields of personal health monitoring, patient rehabilitation, sports monitoring and human motion tracking.

Citation Information

Patent Citations

  • Friction nanometer power generator for converting mechanical energy to electric energy and fabrication method of friction nanometer power generator

    CN109412456A

  • Fiber-based friction nano generator and application thereof

    CN116436334A

  • Flexible friction nano-generator based on super-hydrophobic film and preparation method of flexible friction nano-generator

    CN116915084A

  • Sofa having Movable Back

    KR1020210007693A

  • Technique to enhance the electro-optic coefficient of polymers by using a sol-gel cladding layer to increase poling efficiency

    US20070297708A1

Cited By

  • Rehabilitation training sensing device based on self-powered microneedle array and preparation method and application thereof

    CN120000212A